Fabrication of A Diode-based Salt Solution Sensor - Chin Fhong, Soon; Li, Fang Lai; Zainal, Nurfarina (Emerging Advances in Integrated Technology, 2025)
High blood pressure/hypertension is a severe medical issue among Malaysians that could be reduced by monitoring our salt/sodium intake. One way is to use intraoral salt sensor; this in-mouth method however may cause discomfort and adopts complex and costly fabrication processes. Hence, an external and reusable electronic device, that could be used as a â€œsweat-sensorâ€, is preferred in detecting the sodium intake of the body. In this study, a potentiometric diode-based salt solution sensor was designed and fabricated in order to detect different salt solution concentrations with applied external voltage. A p-n junction diode sensor was successfully designed and fabricated using four consecutive techniques; thermal wet oxidation, photolithography, thermal diffusion and metallization. The average sheet resistance and resistivity of the diode sensor were measured to be 3.50 x 105 Â± 0.66 â„¦â„sq and 3.05 Â± 0.5 â„¦cm respectively. This sensor showed ideal I-V diode characteristics with a knee voltage of 11.5V in forward bias condition and breakdown voltage of -4 V in reverse bias condition. For salt concentration detection, the sensor was able to detect salt concentration changes with respect to current flow, up to 45 mg/mL.